1990
DOI: 10.1111/j.1365-2621.1990.tb03610.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetrathionate Protects Proteolytic Activity of Simulated Papaya Latex and Crude Papain

Abstract: Sodium tetrathionate (TT) was assessed for its possible protection of proteolytic activity (PA) of rehydrated crude papain during drying and storage. The addition of 1% 'IT significantly decreased the loss of PA of rehvdrated crude papain after being oven dried at 55°C. This protection of PA was I.?-20% higher than that from metabisulfite. Crude oauain with 1% 'PI lost 20% of PA and with metabisulfite lost 45% L I of PA in 13 wk at room temperature. Results suggest 'IT may decrease loss of PA during papaya lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…EAR, respectively. These results are similar to those found by Arteaga and Nakai (1990) in their study on the effect of sodium tetrathionate in rehydrated crude papain. They reported that addition of 1&dquo;« sodium tetrathionate decreased significantly the loss of proteolytic activity of rehydrated crude papain after being dried at 55 °C (96,« of the original activity present in rehydrated crude papain was retained).…”
Section: Effect Of Concentration Of Protective Agentssupporting
confidence: 94%
See 3 more Smart Citations
“…EAR, respectively. These results are similar to those found by Arteaga and Nakai (1990) in their study on the effect of sodium tetrathionate in rehydrated crude papain. They reported that addition of 1&dquo;« sodium tetrathionate decreased significantly the loss of proteolytic activity of rehydrated crude papain after being dried at 55 °C (96,« of the original activity present in rehydrated crude papain was retained).…”
Section: Effect Of Concentration Of Protective Agentssupporting
confidence: 94%
“…The chemicals used to determine the effect of concentration were categorized into three groups: (i) antioxidants used in the food industry (Branen, 1990): ascorbic acid, sodium ascorbate, erythorbic acid, sodium erythorbate, TBHQ, rutin, a-tocopherol and 4-hexylresorcinol (Monsalve-González ct c~l., 1995). (ii) additives used to protect enzyme activity of papain: sodium metabisulfite (Ortiz et 171., 1980), and sodium tetrathionate (Arteaga and Nakai, 1990). (iii) sugars that have shown to be good stabilizers of proteins when subjected to different stresses such as freezing, drying, and heating (Arakawa and Timasheff, 1982;Carpenter et al, 1987): trehalose (Roser and Colaco;1993) and sucrose.…”
Section: Sample Preparationmentioning
confidence: 98%
See 2 more Smart Citations
“…It is well know that the thiol group of cysteine is sensitive to oxidation and that papain can be inactivated in the presence of oxygen (Gomes et al, 1997). It is reasonable to think that the formation of the thioimidate with the nitrile protects the cysteine from irreversible oxidation in the same way tetrathionate does (Arteaga and Nakai, 1990).…”
Section: Hydrolysis Of Peptide Nitrilesmentioning
confidence: 98%